Thiamine diphosphate synthesis and redox state indicator in rat brain during of B(1) hypovitaminosis - Yu. M. Parkhomenko; A. S. Pavlova; O. A. Mejenskaya; S. P. Stepanenko; L. I. Chekhivska (The Ukrainian Biochemical Journal, 2017)
The main aim of this study was to reveal the relationship between thiamine metabolism and the redox balance of cellular metabolism in chronic alimentary thiamine deficiency. On the experimental model of chronic alimentary thiamine deficiency (hypovitaminosis) the dynamics of changes in the indicators of thiamine diphosphate (ThDP) synthesis and the redox state in rat brain tissue were studied. In the whole brain homogenate of the rat, the levels of ThDP and thiamine pyrophosphokinase (TPK) activity as well as the levels of free SH-groups and reactive oxygen species (ROS) were measured. The results obtained showed, even with a very limited intake of thiamine into the body (model of alimentary hypovitaminosis), there was no increase in the level of ROS (one of the signs of oxidative stress) in the brain tissue, while the level of free SH-groups significantly decreased. Under these conditions, the content of the coenzyme form of thiamine, ThDP, in brain tissue changes insignificantly, which suggests that there are non-coenzymatic mechanisms of vitamin B1 involvement in maintaining cellular redox homeostasis. The analysis of changes in the ThDP content and the TPK activity in the cerebral cortex, cerebellum and hippocampus of the rats’ brain in the dynamics of hypovitaminosis development and TPK immunoreactivity at the end of the experiment showed that the ThDP synthesis in cells of various brain regions under the indicated conditions does not depend on the redox state, but is regulated by the level of ThDP.